Effect of COVID-19 on the Tourism Industry of Bangladesh: A Qualitative Study on Kuakata Sea Beach - Sultana, Tahiya; Sultana, Most. Sharmin (Journal of Population and Development, 2024)
We must recommend or support the "tourism sector" because it allows us to unwind, enjoy ourselves, be refreshed, and learn new things. This paper aims to examine the Effect of COVID-19 on Bangladesh's tourism industry before and after COVID-19. This is a qualitative study. The paper is based on primary data where we went to root-level people, took their own opinions, and focused on identifying how COVID-19 has affected tour operator organizations (hotels, motels, and restaurants), floating businessmen and tourists at Kuakata.We tried to find out the adjustment strategy of tour operator organizations to overcome the problematic situation the existing conditions of tourism sectors based on consumers' current situation after COVID-19. Non-probability sampling method has been used to choose the sample through convenience sampling and judgment sampling. To collect data face-to-face and telephone in-depth interviews were used. Qualitative content analysis was used for analyzing data. This paper's findings showed that before COVID-19 the traffic of tourists at residential hotels, motels, and restaurants was significant. During the pandemic time, all the activities of tour operators were locked.This paper also found that after COVID-19 the number of tourists increased for Payra Bridge and Padma Bridge which is a positive side. After COVID-19, everyone moves to maintain a hygienic way, but tourists don’t enjoy their time because the side roads and other visitable areas like Lal Kakrar Deep, Fatrar Chor, Jhau Bon, Shutkipolli, Narikel Bagan, etc. haven’t proper transportation system. The findings of the paper will play an important role theoretically and practically.